Some new data concerning the mutagenic action of DNA - Gershenson, S.M.; Alexandrov, Yu.N. (Биополимеры и клетка, 1994)
It is shown that spermatozoa of Drosophila melanogaster can transfer molecules of exogenous DNA (or their fragments) from a solution of this DNA injected into the haemocel of an adult male into the ooplasm of the egg. As a result, mutations induced in the descendants arise both in the paternal and the maternal chromosomes obtained by them. The mutagenic effect of exogenous DNA has a prolonged character inducing mutations in the descendants during many cell generations after DNA-treatment of their father. The mechanism of such a prolongation of the mutagenic action of DNA is discussed.